2003 IEEE Workshop on Applications of Signal Processing to Audio and Acoustics (IEEE Cat. No.03TH8684)
DOI: 10.1109/aspaa.2003.1285820
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between multi-channel audio equalization filters using warping

Abstract: Typically, mom equalization techniques do not focus on designing filters that equalize Ute mom responses at perceptually relevant frequencies. Thus, by performing Bark warping 01 Ute room responses and using lower order spectral models it is possible to design low order psycho-acoustically motivated equalization filters. In this paper, we compare the performance, thmugh experiments, between the traditional RhlS averaging filter (with and without warping lo the Bark scale) and our pattern recognition based mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…A fuzzy c-means clustering method is applied in [30,[70][71][72]121,139,140]. In the approach of [121,139], "representative prototypical room responses" are derived from several measured room responses that share similar characteristics using the fuzzy c-means unsupervised learning method.…”
Section: Clustering Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…A fuzzy c-means clustering method is applied in [30,[70][71][72]121,139,140]. In the approach of [121,139], "representative prototypical room responses" are derived from several measured room responses that share similar characteristics using the fuzzy c-means unsupervised learning method.…”
Section: Clustering Methodsmentioning
confidence: 99%
“…The equalizer is then computed from the inverse of the general point response using LPC analysis, "obtaining a significant improvement in equalization performance over the spatial averaging methods" with the suppression of the peaks in the room magnitude spectra [139]. The method was further improved in [70,71,140] by applying the fuzzy c-means clustering to warped impulse responses, thus taking advantage of the perceptual properties of the ear. The approach was also combined with multirate filtering in [72] to allow effective filtering of the low frequency response at low sampling rates with computational savings.…”
Section: Clustering Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…An objective function that is particularly useful for characterizing the magnitude response is the spectral deviation measure [5], [6]. Given that the effects of the choice of the crossover frequency are bandlimited around the crossover frequency, it will be shown that this measure is quite effective in predicting the behavior of the resulting magnitude response around the crossover.…”
Section: Objective Function Based Crossover Frequency Selectionmentioning
confidence: 99%